Construction Status and Future Development of Rehabilitation Information Service Industry in China - Xiangli CHEN (康复学报)
In this paper, it was to review the domestic digitalization construction and development status in rehabilitation information resources based on the network environment, as well as the establishment and integration of hospital information service system, so as to achieve further development of regional rehabilitation information service system.